Navigating Employment Transformations: Liberalism vs. Statism in the Era of Industry 4.0 - Chuanlin Wang; Guowan Yan; Jing Yang (Amfiteatru Economic)
Industrial Revolution 4.0, with its emphasis on smart manufacturing, has a profound impact on traditional employment. This study aims to examine changes in firms’ employment decisions in the context of Industry 4.0, shedding light on the conflict between liberalism's market mechanisms and statism's government interventions. Given China’s status as the world’s largest emerging market, its unique politico economic structure and the global technological transformation of Industry 4.0 jointly shape a dynamic labor market that requires a balance between government intervention and market forces. Using a sample of publicly listed Chinese companies from 2007 to 2022, we employ a difference-indifferences (DID) approach and ordinary least squares (OLS) estimation to empirically investigate changes in firms’ labor demand under Industry 4.0. To ensure robustness, we perform several other analyses, including parallel trend tests and placebo tests. Our results indicate that Industry 4.0 reduces the overall labor demand of firms, characterized by a decrease in low-skilled workers and an increase in high-skilled workers. Furthermore, a triple difference model reveals that market forces exacerbate the negative employment effects of Industry 4.0, whereas government interventions mitigate these effects to some extent. Our findings offer a new perspective on how Industry 4.0 influences the employment market within the frameworks of statism and liberalism. It also proposes a potential resolution to the conflict between liberalism and statism in the context of Industry 4.0, while providing valuable insight into corporate employment decisions.